A problemática ambiental dos resíduos sólidos urbanos na região Centro-Oeste no período de 2008 a 2017, Brasil - Camargos, Carolina dos Santos (2018)
This study addressed an issue related to the environmental problem of urban solid waste in the central-western region of Brazil, from 2008 to 2018, in order to describe the problems that the generation of these wastes, and the lack of adequate to the environment. The choice of theme is a result of concern about environmental degradation, which has increased in recent years around the world, began to analyze topics such as population growth, lack of environmental responsibility and waste of resources in general, besides the fact of treating the issue of solid waste that has been one of the greatest social problems of mankind, and there is a need for awareness about reducing environmental impacts and preserving nature. In view of this reality, the following problem was addressed: How can the generation and destination of municipal solid waste be made so that it does not cause or at least mitigate environmental impacts? In order to answer the problematic and the scope of the proposed objectives, a bibliographical review was used as a research method, whose function is to analyze articles and scientific works that deal with the researched subject, reaching the result that the management and management of urban solid wastes to apply the concept of sustainability, still values the environment for present and future generations bringing benefits not only environmental but also economic and social.